A Different Musical Perspective: Improving Outcomes in Music through Habilitation, Education, and Training for Children with Cochlear Implants - Rocca, Christine (Seminars in Hearing, 2012)
The musical outcomes for children with cochlear implants (CIs) who have been consistently involved in musical habilitation, education, and training programs, from a young age, may be presenting a new musical perspective. This article aims to provide strategies that professionals may use to improve musical perception for children with CIs in clinical and educational settings. The habilitation and education programs discussed are based on extensive clinical experience and assessments of over a hundred children and teenagers with CIs. Stages of musical development for children with CIs, from beginners to more advanced levels, are described for several key musical areas: (1) vocalization that leads to singing, (2) listening, and (3) general musicality. Practical activities for developing singing, listening, and general musicality are described. Music-based habilitation, education, and training methods may enable children with CIs to participate more fully in all aspects of musical experience.
Keywords: CIs; music; singing; music therapy